2011
DOI: 10.1111/j.1748-8583.2010.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning ageing workers from paid to unpaid work in non-profits

Abstract: Resource constraints and retention issues associated with an ageing workforce have challenged non‐profit institutions. Human resource management professionals in these organisations can stem the loss of organisational learning by developing strong social exchanges that encourage employees to pursue post‐retirement volunteering. This paper developed a conceptual model that described how ageing workers may evaluate and connect the quality of the relationships they build at work through social exchanges to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 63 publications
0
11
0
1
Order By: Relevance
“…It is therefore argued that employers are increasingly required to appreciate and respond to these expectations and requirements in order to maximise each employee's potential contribution towards meeting organisational objectives (Christensen-Hughes and Rog, 2008;Coupland et al, 2008;Sturges, 2008). For example, the CIPD (2006) suggested that organisations might introduce methods of creating opportunities for employee views and opinions to be heard (Christensen-Hughes and Rog, 2008;Gibbons, 2006); developing variable packages of benefits and working conditions (Smith, 2008;Worman, 2006); offering flexible working arrangements Rowley and Purcell, 2001); considering the meaningfulness of the work (Kahn, 1990;May et al, 2004); providing high quality supervisory support (Karatepe and Olugbade 2009;Kim et al, 2009); and, paying particular attention to personorganisation fit (Kristof, 1996;Schlosser and Zinni, 2011).…”
Section: Table 1 -Herementioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore argued that employers are increasingly required to appreciate and respond to these expectations and requirements in order to maximise each employee's potential contribution towards meeting organisational objectives (Christensen-Hughes and Rog, 2008;Coupland et al, 2008;Sturges, 2008). For example, the CIPD (2006) suggested that organisations might introduce methods of creating opportunities for employee views and opinions to be heard (Christensen-Hughes and Rog, 2008;Gibbons, 2006); developing variable packages of benefits and working conditions (Smith, 2008;Worman, 2006); offering flexible working arrangements Rowley and Purcell, 2001); considering the meaningfulness of the work (Kahn, 1990;May et al, 2004); providing high quality supervisory support (Karatepe and Olugbade 2009;Kim et al, 2009); and, paying particular attention to personorganisation fit (Kristof, 1996;Schlosser and Zinni, 2011).…”
Section: Table 1 -Herementioning
confidence: 99%
“…Employee engagement is now actively being recognised as an integral element in any hospitality organisation's talent management strategy. Indeed it has been found that employers are increasingly using the recruitment and selection process as a means of identifying characteristics and traits that prospective employees possess that are indicators of a future committed and engaged worker (Raybould and Wilkins, 2005;Schlosser and Zinni, 2011;Scott and Revis, 2008). A review of the current talent management literature by Christensen-Hughes and Rog (2008) found that increasing numbers of tourism organisations now appear to be taking action to increase employee engagement with a view to minimising employee turnover and increasing both employee satisfaction and organisational commitment.…”
Section: Employee Engagement In the Tourism And Hospitality Industrymentioning
confidence: 99%
“…Finally, volunteering could be either a complement to or a substitute for paid work (Erlinghagen, 2010), depending on the type or area of volunteer work, skills and attitudes developed from the workplace, individual motivations for volunteering, and choice in retirement (Erlinghagen, 2010;Schlosser & Zinni, 2011;Wilson, 2012). For example, volunteer time was measured dichotomously, with 100 hr per year serving as a cutoff point, which definitely cannot capture substantial variability in volunteering efforts.…”
Section: Discussionmentioning
confidence: 99%
“…An organization that values older workers as assets can build a culture of trust and socialize all workers to continuously share ideas and to respect one another for what they have to offer, regardless of their age (Schlosser and Zinni, 2011). Management can ensure that retirees are kept informed about what is going on in the organization.…”
Section: Discussionmentioning
confidence: 99%